Tecnologia de biodigestores rurais e desenvolvimento rural sustentável na região Oeste do Paraná - Soares, Caroline Monique Tietz (2020)
The intensification of Brazilian pig farming has also promoted the production of large amounts of waste that, if handled inappropriately, become a source of pollution to the environment. The use of biodigesters in this context appears as an alternative to mitigate the impacts generated by this activity. Thus, this research aimed to study the current state of the technology of rural biodigesters and their contributions to sustainable rural development in the Western region of Paraná, verifying the factors that are repressing their effectiveness in pig farming, as well as the benefits of this the way it has been used. To this end, the present thesis consists of three articles. The first is dedicated to the use of biogas in rural areas as a factor of sustainable rural development, in the second article the prospects for the technology of anaerobic biodigestion of swine wastewater in the West of Paraná are analyzed based on the SWOT matrix, and in the last article evaluates the system of biodigesters in use in pig farming in Western Paraná and its relationship with sustainability. The general conclusion highlights the high potential of biodigester technology and the benefits resulting from its use, but despite this, there is still a small participation of this in our country. In order to change this scenario, it is essential that the public authorities provide means to encourage this system, since it offers tools to favor sustainable development in rural areas.